2007
DOI: 10.1086/517496
|View full text |Cite
|
Sign up to set email alerts
|

The Masses and Evolutionary State of the Stars in the Dwarf Nova SS Cygni

Abstract: The dwarf nova SS Cygni is a close binary star consisting of a K star transferring mass to a white dwarf by way of an accretion disk. We have obtained new spectroscopic observations of SS Cyg. Fits of synthetic spectra for Roche lobeY filling stars to the absorption-line spectrum of the K star yield the amplitude of the K star's radial velocity curve and the mass ratio, K K ¼ 162:5 AE 1:0 km s À1 and q ¼ M K /M WD ¼ 0:685 AE 0:015. The fits also show that the accretion disk and white dwarf contribute a fractio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 51 publications
4
76
1
Order By: Relevance
“…The value given above is also essentially higher (by a factor of ∼2.5) than the one derived by Schreiber & Gänsicke (2002). The higher mass accretion rate is required because Bitner et al (2007) found a higher value for the inclination and a lower value for the mass of the white dwarf.…”
Section: Accretion Rate During Outburstmentioning
confidence: 58%
See 1 more Smart Citation
“…The value given above is also essentially higher (by a factor of ∼2.5) than the one derived by Schreiber & Gänsicke (2002). The higher mass accretion rate is required because Bitner et al (2007) found a higher value for the inclination and a lower value for the mass of the white dwarf.…”
Section: Accretion Rate During Outburstmentioning
confidence: 58%
“…As a consequence of the revised inclination and mass of the white dwarf (see Table 1), agreement with the DIM now requires distances as short as d < ∼ 100 pc. Bitner et al (2007) (right column). Also given is the derived outer radius of the disc (∼0.9 R 1 ) in units of 10 10 cm.…”
Section: Accretion Rate During Outburstmentioning
confidence: 99%
“…However, we have to point out that a recent estimation gave a lesser WD mass in SS Cyg, M WD = 0.81 ± 0.18 M (Bitner et al 2007) instead of 1 M . We may expect that some BL model around a slower rotating WD with M WD = 0.8 M can have similar effective temperatures (and a similar spectrum) as the considered BL model with M WD = M and ω WD = 0.8ω K .…”
Section: Comparison With Observationsmentioning
confidence: 73%
“…For example, there is very little evidence for even the presence or absence of starspots on CV secondaries. Webb et al (2002) spectroscopically inferred a spot coverage of 20% for the donor in SS Cyg, but the likely nuclearevolved nature of this star (Bitner et al 2007) makes it an unreliable calibration point for our purposes. Similarly, Roche tomography has been used to detect starspots in the donor stars of AE Aqr (Watson et al 2006), BV Cen (Watson et al 2007b), and V426 Oph (Watson et al 2007a), but one of these is a strongly magnetic system (AE Aqr) and at least one of the others contains an evolved donor (BV Cen).…”
Section: Larger-than-expected Radii In Non-interacting Low-mass Starsmentioning
confidence: 99%